2018
DOI: 10.1042/bcj20180402
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into oxidation of medium-chain fatty acids and flavanone by myxobacterial cytochrome P450 CYP267B1

Abstract: Oxidative biocatalytic reactions performed by cytochrome P450 enzymes (P450s) are of high interest for the chemical and pharmaceutical industries. CYP267B1 is a P450 enzyme from myxobacterium So ce56 displaying a broad substrate scope. In this work, a search for new substrates was performed, combined with product characterization and a structural analysis of substrate-bound complexes using X-ray crystallography and computational docking. The results demonstrate the ability of CYP267B1 to perform in-chain hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
(65 reference statements)
2
0
0
Order By: Relevance
“…Similar observations of shifted regioselectivities have been made previously: Jóźwig et al [46] reported that for CYP267B1 from Sorangium cellulosum the regioselectivity of hydroxylation was shifted from positions located closer to the methyl terminal carbon (ω−1, ω−2, ω−3) towards the in-chain positions (ω−3 and ω−4) with increasing chain length of the fatty acid. The authors also found evidence for C14 6 to be bound U-shaped and in two different orientations [46].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar observations of shifted regioselectivities have been made previously: Jóźwig et al [46] reported that for CYP267B1 from Sorangium cellulosum the regioselectivity of hydroxylation was shifted from positions located closer to the methyl terminal carbon (ω−1, ω−2, ω−3) towards the in-chain positions (ω−3 and ω−4) with increasing chain length of the fatty acid. The authors also found evidence for C14 6 to be bound U-shaped and in two different orientations [46].…”
Section: Discussionsupporting
confidence: 87%
“…Similar observations of shifted regioselectivities have been made previously: Jóźwig et al [46] reported that for CYP267B1 from Sorangium cellulosum the regioselectivity of hydroxylation was shifted from positions located closer to the methyl terminal carbon (ω−1, ω−2, ω−3) towards the in-chain positions (ω−3 and ω−4) with increasing chain length of the fatty acid. The authors also found evidence for C14 6 to be bound U-shaped and in two different orientations [46]. Khatri et al [19] investigated fatty acid hydroxylation by CYP267A1 from the same organism and noticed that the wild-type enzyme contains a natural heme-signature variant (a conserved phenylalanine at position 366 exchanged by a leucine residue) that led to a shift in regioselectivity from subterminal (ω−1 to ω−3) positions to in-chain (ω−4 to ω−9) positions.…”
Section: Discussionsupporting
confidence: 87%